Partners wanted for organic insecticide trials - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Our article on organic agriculture in Spore 85 continues to attract responses. Shei W Kanjo, Coordinator of SPACE, PO Box 20, Ndop, NW Province, Cameroon tells us that his organisation is 'made up of nine agricultural and community development...